Investigating how teachers experiences shy children and the strategies Implemented to Include them. - Brennan, Karen (My University, 2019)
Shyness is something most people will experience at some point in their lives. For some, it will come and go without much effect. For others it is something much more than a passing emotion or a preference for quietness and solitude. Previous research has taught us that childhood shyness can inhibit some children's growth and affect their development both personally, academically and mentally if it goes untreated. This research study explores the experiences and perceptions that practicing primary school teachers have of shy children. Its aim was to provide an insight into how teachers view and perceive shyness and the interventions or methods teachers implement in order to facilitate and include shy children in the classroom. The research study was conducted through a qualitative lens over a two-week period and data was collected through one-to-one semi-structured interviews from practicing primary school teachers. The findings of this study suggest that a teacher's own personal experience of shyness may affect how seriously they view the effects of childhood shyness and how they conceptualise shyness. It may be that teachers who still identify as shy and experience the effects of shyness, view it as a more detrimental issue for the children that experience it than non-shy teachers. The findings also imply that further research in an Irish context is warranted and that more information on the inner-workings and struggles that shy children experience should be available to teachers.
Professional Masters of Education
Keywords: Research Subject Categories